Http Streaming Based Ajax Player (International Journal of Engineering and Computer Science, 2015)
In the previous couple of years streaming of video on the web has encountered quick development and will keep on expanding in significance as broadband innovations and authoring tools keep on making strides. As the internet turns into an inexorably famous alternative to traditional communications media, internet streaming will turn into a critical segment of numerous content providers’ communications strategy. In this paper we proposed a solution to HTTP live streaming, which assesses the weights of media segments to choose the transmitting needs taking into account the present playing time and alter the proper transmission path.